The nutritional value of edible freshwater Alga Cladophora sp. (Chlorophyta) grown under different phosphorus concentrations - Khuantrairong T. (2017)
Culture of an edible freshwater alga Cladophora sp. was subjected to phosphorus (P) supply (1.07-14.78 mg L -1 of PO 4 -P) in order to determine its proximate compositions, vitamins, minerals and carotenoid compositions. The alga was mass cultured by using 10% of canteen wastewater with the addition of di-potassium hydrogen orthophosphate at the concentrations of 0, 5, 10, 15 and 20 mg L -1 . The results showed that with increased P concentration, protein, vitamin A, P, β-carotene, lutein and zeaxanthin contents increased but carbohydrate content decreased indicating that P supply could enhance carotenoid production and some nutritional values of this alga. © 2011 Friends Science Publishers.